2012
DOI: 10.1134/s0038094612040016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of secular resonances on the long-term orbital evolution of uncontrollable objects on satellite radio navigation systems in the MEO region

Abstract: We present the results of the study of long term orbital evolution of space debris objects, formed from end of life space vehicles (SV) of satellite radio navigation systems in the medium Earth orbit (MEO) region. Dynamical features of the evolution of objects in this region have been studied on the basis of 20 year laser surveillance with the Etalon 1 and Etalon 2 satellites and the results of numerical simulation of the long term evolution of operating and disposal orbits of uncontrolled GLONASS and GPS SVs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…So, we can say that the particle is in vicinity of the resonances but is not captured by them. Mean motion resonance is unstable and may be reason of the chaotic motion (Chirikov, 1979, Bordovitsyna et. al, 2012, Bordovitsyna et.…”
mentioning
confidence: 99%
“…So, we can say that the particle is in vicinity of the resonances but is not captured by them. Mean motion resonance is unstable and may be reason of the chaotic motion (Chirikov, 1979, Bordovitsyna et. al, 2012, Bordovitsyna et.…”
mentioning
confidence: 99%
“…As known (Murray and Dermott, 2009), the perturbing function describing the effect of the third body on an asteroid can be expressed in terms of orbit elements as follows (Bordovitsyna et. al., 2012):…”
Section: Algorithm For Identifying the Apsidal-nodal Resonancesmentioning
confidence: 99%
“…Allan and Cook (1964) warned that circular motion may be unstable for some inclinations due to the Kozai-Lidov effect or luni-solar resonance in general (Breiter 2001). Recently, a series of papers showed that the eccentricity of the orbits for Global Navigation Satellite System (GNSS) may increase exponentially (Chao and Gick 2004;Bordovitsyna et al 2012). Through theo-retical calculations and numerical verifications for the Chinese BeiDou Inclined Geosynchronous Earth Orbit (IGSO), we found that the eccentricity of the nearcircular IGSO satellite with an initial inclination not larger than 32 • can always remain small in the longterm evolution, and the initial Right Ascension of the Ascending Node (RAAN) can affect the eccentricity too (Zhao et al 2015).…”
Section: Chang-yin Zhaomentioning
confidence: 99%